(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
The present KAP study aimed to ascertain the knowledge, attitudes, and practices on clinical toxicology among internees and medical doctors at ACSR Govt. Medical College & Hospital, Nellore, Andhra Pradesh, India, in the light of implementing new National Medical Commission curriculum (Graduate Medical Regulations 2019). The study also aimed at understanding the knowledge and training gaps pertaining to clinical toxicology in the target population and thereby propose interventions for proper delivery of toxicology curriculum. A semi structured questionnaire was used to elicit information wherein 120 health care providers voluntarily participated in the study. The results detected significant deficits towards understanding concepts in clinical toxicology and implementation of evidence-based approach in providing care. Our study identified the need to stress on toxidrome based approach, use of evidence-based decontamination methods, the necessity to stabilise the patient more than being enthusiastic in diagnosing the poisoning, increased use of multidose activated charcoal as a primary antidote, use of poison control centre helpline, material safety data sheet & toxicology databases when in doubt, employing holistic care models, providing education on social & preventive toxicology and role of screening in chronic paediatric poisonings.